Programme Vitam: a cross-departmental project developing a free software for digital archives and records preservation, bringing together archivists, records managers and IT professionals. Issue 1 (January 2018) - Rebours, Mélanie
Abstract : Programme Vitam is a French cross-departmental project that aims to develop an open-source, back-end software to manage and preserve digital records and archives. The project has been drawn up and organized using an innovative approach in France, involving records managers, archivists and IT professionals, and represents the first effort of different public agencies coming together to initiate a digital records and archives project. Other public agencies have joined the project, either to brainstorm or to implement the software as a new tool in their digital repositories. The Programme Vitam team is tackling many challenges. It is responsible for uniting teams from different agencies and professions, and making collaboration closer and as participatory and efficient as possible. Its goal is to allow free rein to creativity and inventiveness, in order to develop the simplest and most innovative product possible. The software development project utilizes Agile methodology. This article reports on the Vitam team's panel session at the ICA Congress 2016, which linked to the theme of Recordkeeping in the Digital Age. The panel brought together archivists and IT professionals in order to provide feedback on their way of working and to report on the first achievements of the project.